PERAN TRANSFORMASI DIGITAL DAN ORIENTASI PASAR DALAM MEMPENGARUHI KEUNGGULAN BERSAING DAN KINERJA PEMASARAN UMKM - Kusumo, Haryo; Achmad Solechan; Susatyono, Jarot Dian; Andriana, Myra; Novianto, Rizki (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
This study aims to examine the influence of digital transformation and market orientation on the marketing performance of MSMEs, with competitive advantage as an intermediary, in MSMEs in Semarang Regency. The sample of this study consists of 70 MSMEs selected through purposive sampling, based on the following criteria: MSMEs that use digital marketing, have been operating for at least 2 years, and are willing to complete the questionnaire. Data were collected through questionnaires and analyzed using SmartPLS software. The results of the study indicate that digital transformation and market orientation significantly enhance the competitive advantage of MSMEs. Additionally, digital transformation, market orientation, and competitive advantage have a positive and significant impact on the marketing performance of MSMEs. Competitive advantage is proven to mediate the influence of digital transformation and market orientation on the marketing performance of MSMEs.